Isolation and purification of Bacillus thuringiensis var. israelensis IМV В-7465 peptidase with specificity toward elastin and collagen - N. А. Nidialkova; L. D. Varbanets; V. O. Chernyshenko (The Ukrainian Biochemical Journal, 2016)
Peptidase of Bacillus thuringiensis var. israelensis IМV В-7465 was isolated from culture supernatant using consecutive fractionations by an ammonium sulphate (60% saturation), ion-exchange chromatography and gel-filtration on the TSK-gels Toyoperl HW-55 and DEAE 650(M). Specific elastase (442 U∙mg of protein-1) and collagenase (212.7 U∙mg of protein-1) activities of the purified enzyme preparation were 8.0- and 6.1-fold, respectively higher than ones of the culture supernatant. Peptidase yields were 33.5% for elastase activity and 30.1% for collagenase activity. It was established that the enzyme is serine metal-dependent alkaline peptidase with Mr about 37 kDa. Maximal hydrolysis of elastin and collagen occurs at the optimum pH 8.0 and t° – 40 and 50 °С, respectively. The purified preparation has high stability at pH in the range of 7.0 to 10.0 and 40-50 °С.